2023
DOI: 10.3390/su15076097
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Analysis of a Photovoltaic Power Source Interfacing a Current-Mode-Controlled Boost Converter with Limited Current Sensor Bandwidth for Maximum Power Point Tracking

Abstract: The presence of a high ripple in the inductor current of a DC-DC converter in a photovoltaic converter chain leads to a considerable decrease in the energy efficiency of the converter. To solve this problem, we consider a current-mode control and for economic reasons we used a single inductor current sensor with a low-pass filter. The purpose of the low-pass filter is to minimize the effect of ripple in the inductor current by taking only the DC component of the signal at the output of the sensor for tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Furthermore, on the curve in Figure 7a we notice that the boundary between period-1 oscillations and subharmonic oscillations is at V M = 0.4V. This result is significantly better than the findings of Kengne et al in [51], where they presented a current mode controller that uses a low-pass filter after the inductor current sensor. They showed that as the filter frequency tends towards infinity (i.e., no filter), the boundary between subharmonic oscillations and period-1 oscillations converges to V M = 0.5V.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, on the curve in Figure 7a we notice that the boundary between period-1 oscillations and subharmonic oscillations is at V M = 0.4V. This result is significantly better than the findings of Kengne et al in [51], where they presented a current mode controller that uses a low-pass filter after the inductor current sensor. They showed that as the filter frequency tends towards infinity (i.e., no filter), the boundary between subharmonic oscillations and period-1 oscillations converges to V M = 0.5V.…”
Section: Discussionmentioning
confidence: 55%
“…They showed that as the filter frequency tends towards infinity (i.e., no filter), the boundary between subharmonic oscillations and period-1 oscillations converges to V M = 0.5V. This result shows that the average current mode control presented in this work is better for the stabilization of a photovoltaic converter string than the one developed by Kengne et al in [51]. We can also mention that, as with most works in the literature, appropriate linearization of the PV generator model does not affect the accuracy of the model in predicting the period-doubling bifurcation of the system.…”
Section: Discussionmentioning
confidence: 56%
“…In (Lee et al, 2000), interleaved operation of two or more boost converters is presented in this study for high-power applications to increase output power and reduce output ripple (Lee et al, 2000;Kengne et al, 2023). Two structures, a switched-capacitor (SC)based boost converter and a two-level inverter, are connected in cascade in this article (Axelrod et al, 2005).…”
mentioning
confidence: 99%